The last of the Cheju divers - Waring, Rob; Heinle Cengage Learning (London : Heinle, Cengage Learning/National Geographic, 2008)
Cheju is South Korea is known for its women divers. They have dived into the ocean to look for seafood for a long time. It's dangerous, but there were no other jobs available
Title from title screen
Video and audio on DVD
Pre-intermediate 1000 headwords
DVD format
Optional audio and subtitle in American English or British English
Keywords: Geography